The anxiolytic properties of vernonia amygdalina (asteraceae) in laboratory mice (2016)
Anxiety is a state of excessive fear and is characterized by motor sympathetic hyperactivity, apprehension and vigilance syndromes. Vernonia amygdalina commonly called bitter leaf, belongs to the family Astaraceae, and has been reported to be used locally in the treatment of psychiatric challenges. However, no work has been reported on pharmacological potentials of ethyl acetate fraction of Vernonia amygdalina on anxiety. This study was therefore designed to investigate the effect of ethyl acetate fraction Vernonia amygdalina (EAVA) on anxiety status in mice. The air-dried leaves of Vernonia amygdalina (VA) pulverized and macerated in methanol for 72 hours, before the extract was partitioned into n-hexane and ethyl acetate fractions. The anxiolytic-like effect of EAVA was investigated using the elevated plus maze (EPM), elevated zero maze (EZM) and light- dark test (LDT). The results obtained were expressed as mean ± S.E.M. Data were analyzed using One-way Analysis of Variance (ANOVA), followed by Newman-Keuls' multiple comparisons test, P<0.05. Vernonia amygdalina showed anxiolytic-like effect in mice, 50- 100mg/kg were significantly different from control by the time spent in the open arms in elevated plus maze and elevated zero maze, and the time spent in light chamber in the light-dark test. In conclusion, this study has shown that ethyl acetate fraction from Vernonia amygdalina possess anxiolytic-like effects. However, further work need to be done to ascertain its mechanism of action.